Estado actual del uso de antihelmínticos en programas de control de las parasitosis intestinales. - Bigi F., Francisco (Revista de Biología Tropical, 1962)
The relative importance of intestinal parasitoses m human populations is commented upon. Surveys show the existence of millions of cases throughout the world; while this is a measure of the importance of the problem, the fact that such high incidence does not seriously affect the life of human communities tends to diminish its relative gravity. There are, however, enough cases of serious disability derived from parasitoses, especially in the tropics, for the matter to be regarded as an important health problem. Control methods employed, although helpful, have not significantly altered the general incidence of parasitoses. Data are reviewed which indicate that, at present, ascariasis is an eradicable human disease, the means being mass treatments of piperazin repeated monthly. The decision to carry out such eradication campaigns appears to depend on economic considerations. There is hope that drugs, as effective against other intestinal parasites as piperazine is against Asear;s, may be developed in the future, and the possibility of a wider eradication of parasitoses wi11 be at hand.